Prevalence of visceral leishmaniasis, risk factors and associated disorders: Knowledge of inhabitants and professionals in Fulbaria, Mymensingh (Bangladesh Journal of Zoology, 2017)
A total of 215 cases were recorded from the rural areas of Fulbaria upazila during June 2015 to May 2016. The prevalence of kala-azar was higher in male (51.22%) than female (36.96%). In the area, 10.1 - 20 years age group was the most prevalent group and the prevalence was found to decrease with the increase of age. Post Kala-azar Dermal Leishmaniasis (PKDL) was developed in 38.14% of kala-azar patients of Fulbaria upazila. The prevalence of kala-azar was found 63.89% in mud house dwellers and when living in tin shed house but with earthen floor, the prevalence was 58.79%. On the other hand, 10.31% had single infection with kala-azar, 21.65% had double infection and 68.04% had multiple infection. Living in proximity to prior case, climatic change, racked mud house, humid area, cattle sheds made of cracked mud walls, lack of awareness and knowledge regarding kala azar were the risk factors. Total 45 professionals were interviewed in the Upazila Health Complex and Upazila Sub-Centers of the study area through a preset questionnaire. Of them, 71.11% had the appropriate acquaintance about the agent (Leishmania donovani) of kala-azar and 35.29% professionals had the correct comprehension regarding the reservoir of kala-azar (man). Most of them (91.11%) recommended rK 39 dipstick test as the single most important diagnostic blood test and Miltefosine and Amphotericin B are the most recommended drugs for treatment of kala-azar.Bangladesh J. Zool. 45(1): 73-83, 2017